Article Review: Development of a new type of TB vaccine as a replacement for the BCG vaccine - Sutanti, B. Novia Rahmadita; Ramdha, Ika Salsabila; Rizki, Alpha Alfi; Putri, Latifa Rahma; Lestari, Neli Aulia; Syaharani, Ninda; Sunarwidhi, Anggit Listyacahyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Tuberculosis (TB) remains a significant global public health threat. The existing BCG vaccine has limited effectiveness, particularly in preventing pulmonary TB in adults. This study aims to review the recent developments in the creation of new TB vaccines as alternatives to BCG. This research employs a systematic review method by collecting articles from the Google Scholar database. Inclusion criteria included articles published between 2014-2024 that are relevant to the development of new TB vaccines. Data analysis was conducted descriptively to identify potential vaccine candidates. Several new TB vaccine candidates have shown promising results, including TAT-Ag85B, MTBVAC, rBCG-LTAK63, and subunit vaccines such as Ag85A and LT70. These vaccines demonstrated increased immune responses and better protection compared to BCG in preclinical trials. Innovative approaches like the use of nanocarriers and prime-boost strategies also show potential in enhancing vaccine efficacy. The development of new TB vaccines indicates significant progress with several potential candidates that could replace or complement the BCG vaccine. However, further research is needed to evaluate the efficacy and safety of these vaccines in clinical trials in humans before they can be widely implemented.